2015
DOI: 10.1007/s10725-015-0080-8
|View full text |Cite
|
Sign up to set email alerts
|

Altered tetrapyrrole metabolism and transcriptome during growth-promoting actions in rice plants treated with 5-aminolevulinic acid

Abstract: As a precursor of chlorophyll, 5-aminolevulinic acid (ALA) acts as a growth-promoting factor in plants, but little is known of molecular basis of plant growth action. The exogenous supply of an optimal concentration of 75 lM ALA without photooxidative risks, as indicated by a negligible change in conductivity, increased dry shoot biomass of rice up to 16 % after 10 days of ALA treatment, compared to the untreated control. Although rice plants treated with ALA gradually increased levels of ALA-synthesizing capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Proved by research in the chlorophyll-deficient mutant of Chlamydomonas reinhardtii, the levels of mRNA and protein output of ChlH are both increased while ChlI and ChlD remained unalterable from dark condition to light (Chekounova et al 2001). Then, Mg-protoporphyrin IX methyltransferase (MgMT) devolves a methyl group from S-adenosyll-methionine to Mg-Proto IX, giving Mg-protoporphyrin IX monomethyl ester (Mg-Proto IX ME) (Nguyen et al 2016). Followed by Mg-protoporphyrin IX monomethyl ester cyclase (MgCy), the reaction merges atomic oxygen (O) to Mg-Proto IX ME and creates 3,8-divinyl protochlorophyllide.…”
Section: Chlorophyllmentioning
confidence: 99%
“…Proved by research in the chlorophyll-deficient mutant of Chlamydomonas reinhardtii, the levels of mRNA and protein output of ChlH are both increased while ChlI and ChlD remained unalterable from dark condition to light (Chekounova et al 2001). Then, Mg-protoporphyrin IX methyltransferase (MgMT) devolves a methyl group from S-adenosyll-methionine to Mg-Proto IX, giving Mg-protoporphyrin IX monomethyl ester (Mg-Proto IX ME) (Nguyen et al 2016). Followed by Mg-protoporphyrin IX monomethyl ester cyclase (MgCy), the reaction merges atomic oxygen (O) to Mg-Proto IX ME and creates 3,8-divinyl protochlorophyllide.…”
Section: Chlorophyllmentioning
confidence: 99%
“…Therefore, photosynthetic capacity of photosystems II (PS II) was enhanced by increasing light-harvesting pigments in our study. Exogenous ALA increased the content of chlorophyll in rice ( Oryza sativa L.) ( Nguyen et al, 2016 ). Subsequently, we also noticed that at stressful condition, heme content and HEMH expression were not reduced to the level of CK.…”
Section: Discussionmentioning
confidence: 99%
“…5-aminolevulinic acid (ALA) has been considered as a growth regulator or potential plant hormone in higher plants. Its promotive role in enhancing plant biomass, photosynthesis and fruit quality under normal growth condition has been confirmed in rice ( Oryza sativa L.) ( Nguyen et al, 2016 ), strawberry ( Fragaria ananassa Duch.) ( Sun et al, 2017 ), and peach ( Prunus persica L.)( Ye et al, 2017 ).…”
Section: Introductionmentioning
confidence: 93%
“…Zhang et al (, ) approved that either over‐production of endogenous ALA in YHem1 transgenic Arabidopsis or exogenous ALA treatment in tomato seedlings resulted in more heme accumulation under salt stress. Recent reports on RNA‐seq have shown that the improvement of ALA in plant stress tolerance is associated with its own promotion of tetrapyrrole metabolism (Nguyen et al , Niu and Ma , Wu et al , Xiong et al ). Therefore, one or more components in ALA metabolic pathways may be involved in the regulation of plant tolerance against salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…ALA has been found to induce antioxidant enzyme activities (Nishihara et al , Akram and Ashraf ), as well as nonenzymatic antioxidant substances, such as ascorbate, glutathione, proline and polyphenols, which are involved in the elimination of excess ROS and the prevention of oxidative stress (Wongkantrakorn et al , Al‐Ghamdi and Elansary ). Recently, several studies have emphasized that the mechanism of ALA‐improved plant stress tolerance is associated with the promotion of tetrapyrrole metabolism (Nguyen et al , Niu and Ma , Wu et al , Xiong et al ). These are in agreement with our previous study, where Wang et al () found that the germination of pak choi seeds, promoted by ALA under salinity, depended on its conversion into tetrapyrroles.…”
Section: Introductionmentioning
confidence: 99%